Pelatihan Menyusun Menu Gizi Seimbang pada Ibu Balita Stunting di Desa Bajoe, Konawe: Training on Developing Balanced Nutrition Menu for Stunting Mothers of Under-Five Children in Bajoe Village, Konawe - Rasmaniar Rasmaniar; Euis Nurlaela; Kasmawati Kasmawati; Nurbaya Nurbaya (Poltekita: Jurnal Pengabdian Masyarakat, 2022)
Stunting can cause delays in motor development which includes emotional development, behavior, and brain development among under-five children. Mother's knowledge is closely related to the nutritional status of the children. The inadequate practice of feeding infants and children (IYCF) is influenced by the mother's low level of knowledge. Therefore, this community service activity aimed to increase mothers' knowledge about the importance of balanced nutrition and improve mothers' skills in compiling a balanced nutritional menu from local food ingredients. This activity was carried out in Bajoe Village, Soropia District, Southeast Sulawesi. As many as 35 mothers were involved as participants. The form of this activity was counseling and practice of compiling a balanced nutrition menu. The counseling method was delivered in the form of lectures and discussions. The evaluation was done in the form of pre-test and post-test. The results of the pre-test showed the mean score was 76.28, and there was an increase in the post-test score to 93.43. It means that there was an increase in the score of 17.15 points. Assistance to mothers in providing a balanced nutritional menu is important to support the growth and development of children.   ABSTRAK Stunting pada balita dapat mengakibatkan keterlambatan perkembangan motorik yang meliputi perkembangan emosi, tingkah laku, dan perkembangan otak. Pengetahuan ibu sangat berhubungan dengan status gizi balita. Praktik pemberian makanan pada bayi dan anak (PMBA) yang kurang optimal dipengaruhi tingkat pengetahuan ibu yang rendah. Oleh karena itu,  kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan ibu tentang pentingnya gizi seimbang dan meningkatkan keterampilan ibu dalam menyusun menu gizi seimbang dari bahan pangan lokal. Kegiatan ini dilaksanakan di Desa Bajoe, Kecamatan Soropia, Sulawesi Tenggara. Sebanyak 35 ibu balita terlibat sebagai peserta. Bentuk kegiatan ini adalah penyuluhan dan praktik menyusun menu gizi seimbang. Metode penyuluhan disampaikan dalam bentuk ceramah dan diskusi. Evaluasi dilakukan dalam bentuk pemberian pre- dan post-test.  Hasil pre-test menunjukkan rerata skor sebanyak 76,28 dan terjadi peningkatan skor post-test menjadi 93,43. Hal ini berarti terjadi peningkatan skor sebanyak 17,15 poin. Pendampingan pada ibu balita dalam memberikan menu gizi seimbang pada balita sangat penting untuk mendukung tumbuh kembang balita.